Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fphar.2020.00057
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Kappa Opioid and Dopamine Systems in Compulsive Behaviors

Abstract: dopamine and sensitized D2R. Thus, the time-dependent activation of KOR impacts directly on dopamine levels affecting the tuning of motivated behaviors. This review analyzes the contribution of the kappa opioid system to the dopaminergic correlates of compulsive behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 129 publications
(178 reference statements)
0
25
0
Order By: Relevance
“…Furthermore, in humans, KOR agonists could produce a dissociative-like syndrome, a state occurring during an inescapable traumatic experience ( Lanius et al, 2018 ). These dysphoric effects are thought to be the consequence of a dopamine (DA) depletion in the reward and the fear circuits ( Karkhanis et al, 2017 ; Lanius et al, 2018 ; Escobar et al, 2020 ). KOR have been found to be expressed in DA neurons of the nucleus accumbens (NAc), the ventral tegmental area (VTA), the caudate putamen and the substantia nigra ( Chen et al, 2020 ).…”
Section: The Dynorphin/kappa-opioid Receptor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in humans, KOR agonists could produce a dissociative-like syndrome, a state occurring during an inescapable traumatic experience ( Lanius et al, 2018 ). These dysphoric effects are thought to be the consequence of a dopamine (DA) depletion in the reward and the fear circuits ( Karkhanis et al, 2017 ; Lanius et al, 2018 ; Escobar et al, 2020 ). KOR have been found to be expressed in DA neurons of the nucleus accumbens (NAc), the ventral tegmental area (VTA), the caudate putamen and the substantia nigra ( Chen et al, 2020 ).…”
Section: The Dynorphin/kappa-opioid Receptor Systemmentioning
confidence: 99%
“…In this review, we thus focus on both preclinical and clinical research related to the modulation of the KOR system, and its endogenous ligand dynorphin (DYN), in relation with stress and addiction. The interest for this topic has been growing recently ( Helal et al, 2017 ; Karkhanis et al, 2017 ; Jacobson et al, 2018 ; Lanius et al, 2018 ; Valentino and Volkow, 2018 ; Beck et al, 2019 ; Margolis and Karkhanis, 2019 ; Tejeda and Bonci, 2019 ; Anderson, 2020 ; Escobar et al, 2020 ; Nagase and Saitoh, 2020 ). We will thus list here some of the most relevant literature on the DYN/KOR system in pain, dysphoria and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KOR is essential for emotional regulation. Studies have shown that the endogenous opioid peptide dynorphin activates KOR in the nucleus accumbens and KOR agonists inhibit dopamine (DA) transmission ( 86 ). By contrast, KOR antagonists increase the release of basal DA and may produce antidepressant-like effects ( 35 ).…”
Section: Expression and Physiological Function Of Kormentioning
confidence: 99%
“…The trans-3,4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl)cyclohexyl]-benzeneacetamide derivative U-50,488 is a selective KOR agonist, possessing analgesic, cough suppressant, and diuretic properties. It also suppresses the psychostimulant reward through the inhibition of dopamine signaling in the addiction pathways [ 10 , 11 , 12 ], with obvious influence in decreasing amphetamine-induced psychomotor disturbances [ 13 ], in preventing cocaine [ 14 ] or nicotine-induced motor troubles [ 15 ], and in reducing the charges of morphine [ 16 ] or fentanyl [ 17 ] self-administration in rodents. Other research has evidenced the beneficial effects of U50,488 on L-dopa attenuation of motor dyskinesia in rodents and primates with experimental-induced Parkinsonian manifestations [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%